Evaluation of the Prevalence of Punctate White Matter Lesions in a Healthy Volunteer Neonatal Population - Kular, S.; Holmes, H.; Hart, A.; Griffiths, P.; Connolly, D. (American Journal of Neuroradiology, 2022)
SUMMARY: Hypoxic-ischemic injury is the most common cause of neonatal encephalopathy. T1-weighted punctate white matter lesions have been described in hypoxic-ischemic injury. We have reviewed a healthy volunteer neonatal population to assess the prevalence of punctate white matter lesions in neonates with no clinical signs of hypoxic-ischemic injury. Fifty-two subjects were scanned on a neonatal-specific 3T MR imaging scanner. Twelve patients were excluded due to the lack of T1-weighted imaging, leaving a total of 40 patients (35 term, 5 preterm) assessed in the study. One had a solitary T1-punctate white matter lesion. We concluded that solitary punctate white matter lesions have a low prevalence in healthy neonates.HIIhypoxic-ischemic injuryPWMLpunctate white matter lesionSDHsubdural hematoma